Compact and extended objects from self-interacting phantom fields - Dzhunushaliev, Vladimir; Folomeev, Vladimir; Makhmudov, Arislan; Urazalina, Ainur; Singleton, Douglas [UNESP]; Scott, John (American Physical Society (APS), 2016)
In this work, we investigate localized and extended objects for gravitating, self-interacting phantom fields. The phantom fields come from two scalar fields with a wrong-sign (negative) kinetic energy term in the Lagrangian. This study covers several solutions supported by these phantom fields: phantom balls, traversable wormholes, phantom cosmic strings, and phantom domain walls. These four systems are solved numerically, and we try to draw out general, interesting features in each case.